Applications of diode laser in periodontal therapy – clinical guidelines and tips - Vijay Bakshi, Purva; Raghavendra Kulkarni, Mihir; Badrinarayan Setty, Swati (Brazilian Dental Science, 2022)
The diode lasers have become popular clinical tools because of their compact size, affordability, ease of use and versatility. The aim of this paper is to put forth the various applications of a diode laser in day to day practice and highlight the technical aspects of diode laser use for the same. This case series reports management of six different clinical situations with diode laser namely – ankyloglossia, periodontal pocket, unequal gingival zeniths, mucocele, dentinal hypersensitivity and hyper-pigmented gingiva. The patients were treated with 940 nm diode laser with power settings from 0.5 W to 2 W depending on the case. The post-operative healing was uneventful in most cases and favourable outcomes were observed. The diode laser offered surgical advantages like – dry field, disinfection of surgical site and suture-less surgery. In addition, the authors observed better patient satisfaction owing to minimal post-operative pain or swelling and immediate relief in case of dentinal hypersensitivity. This paper presents both surgical and non-surgical applications of diode laser along with the technical aspects. Even though the available literature does not lend substantial evidence for direct comparison of diode laser with conventional techniques, it is safe to conclude that diode laser is an efficient tool for routine use in dentistry. KEYWORDS Laser therapy; Gingivectomy; Ankyloglossia; Periodontal pocket; Dentin sensitivity; Esthetics dental.